Nikonion w opisie Strabona: Nikonion in the Text of Strabo - Mielczarek, Mariusz (Acta Archaeologica Lodziensia, 2019)
The political, economic and social history of ancient Nikonion, a Greek city (polis) located on left bank of the the present day Dniester liman (at the norther border of the village Roxolany, Odessa obl.), can be study practically solely on the basis of material uncovered during archaeological excavations. Ancient, Greek and Roman written surces are few. Among them the description of the Lower Dniester region by Strabo deserves apecial attention. The text is the subject of reflections presented below.